Penerapan Model Pembelajaran Kooperatif Tipe TGT (Teams Games Tournament) untuk Meningkatkan Keaktifan Belajar PKN Peserta Didik Kelas II-B SDN 1 Bengkel - Dzulkhairani, Intan; Izur Mizwar; Ilham (Mataram University, 2024)
This research was conducted on class II-B students at SDN 1 Bengkel in PKN learning process. The Aims of this reasearch is to increase the students activity by using cooperative learning type Teams Games Tournament (TGT). This research used Classroom Action Research (PTK) with two cycles, data on student activity was collected and analyzed qualitatively. The results show a significant increase in students' learning activeness from pre-cycle activities to cycle II. The average percentage of active learning increased from 36% in the pre-cycle, to 45% in cycle I and reached 89% in cycle II. This confirms that the implementation of the Teams Games Tournament (TGT) type cooperative learning model is effective in increasing the activeness of PKN learning for class II_B students at SD Negeri 1 Bengkel.